Customer order flow, information and liquidity on the Hungarian foreign exchange market - Áron Gereben; György Gyomai; Nobert Kiss M. (Magyar Nemzeti Bank, 2006)
Customer order flow - signed transaction volume between market makers and their customers - is a key concept in the microstructure approach to exchange rates. We attempt to explore what the data tells us about the role of customer order flow in the market for Hungarian forint, using the standard analytical framework of the FX microstructure literature. Our results confirm that customer order flow helps to explain exchange rate fluctuations, which suggests that customer order flow is a key source of information for the market makers. We also find that domestic and foreign customers play significantly different roles on the euro/Hungarian forint market: foreign players' order flow seems to provide the information that drives exchange rate fluctuations, whereas domestic customers are the source of market liquidity. We present evidence suggesting that current order flow from customers is able to provide a significantly better `forecast' for the the exchange rate than the random walk benchmark in a simple Meese-Rogoff-type framework. However, we were unable to improve upon the random walk in a more realistic forecasting exercise. Finally, we highlight some features of our data that suggest that beyond microstructure, the traditional portfolio-balance channel of exchange rate determination is also in place.
Keywords: F31; G15; 330; customer order flow; microstructure; exchange rate; Devisenmarkt; Auftrag; Spotmarkt; Derivat; Schätzung; Ungarn